Interaction Between Cortical Auditory Processing and Vagal Regulation of Heart Rate in Language Tasks: A Randomized, Prospective, Observational, Analytical and Cross-Sectional Study - de Góes, Viviane B. [UNESP]; Frizzo, Ana Claúdia F. [UNESP]; Oliveira, Fernando R.; Garner, David M.; Raimundo, Rodrigo D.; Valenti, Vitor E. [UNESP] (Springer Nature, 2019)
Cortical auditory evoked potentials (CAEP) throughout a language task is beneficial during psychophysiological evaluation to advance identification of language disorders. So as to better comprehend human communication and to provide additional elements for neuropsychological examinations we aimed to (1) examine the influence of language tasks on cortical auditory processing and vagal control of heart rate and (2) to verify a possible association between the parasympathetic cardiac regulation and cortical auditory processing in language tasks. This study was completed with 49 women. The subjects were separated into two groups: (1) phonological language tasks (N = 21) and (2) semantic (N = 21) language tasks. Heart rate variability (HRV) and CAEP were evaluated before and after the tests. HRV reduced (small effect size) and P3 wave latency increased after the phonological task. Identical variables were significantly correlated after the phonological task and linear regression indicated significant interaction between pNN50 (percentage of adjacent RR intervals with a difference of duration greater than 50 milliseconds) and P3 latency (16.9%). In conclusion, phonological language tasks slightly reduced parasympathetic control of HR and increased cognitive effort. The association between HRV and CAEP are anticipated to be involved in this mechanism.